Analisis Perbandingan Prediksi Kebangkrutan pada Perusahaan Perbankan di BEI - Irawan, Wreda Adi; Fajri, Aminul (Majors Accounting, Faculty of Economics and Business, Universitas Pancasakti Tegal, 2021)
This study aims to determine the results of predictions for bankruptcy of banking companies listed on the IDX in 2017-2019 using the Altman Z-Score, Springate, Ohlson, Grover, and Zmijewski methods. To analyze and test whether there are differences in the calculation results between the Altman, Springate, Ohlson, Grover, and Zmijewski methods in predicting bankruptcy in banking companies listed on the IDX in 2017-2019. And to find out which method is the most accurate in predicting bankruptcy in banking companies listed on the IDX in 2017-2019. The population used in this study were all banking companies listed on the IDX for the period 2017-2019. The sample in this study were 16 companies selected with certain criteria by purposive sampling method. The data in this study are quantitative data. The data sources in this study are secondary sources obtained from the annual financial statements published from the Indonesia Stock Exchange for the 2017-2019 period. Data collection techniques use documentation techniques. The data analysis method used descriptive statistical techniques, normality tests, hypothesis testing by paired sample t-test and prediction model accuracy tests, the results of the study show that there are significant differences between the Altman, Springate, Ohlson, Grover, and Zmijewski methods and there are methods with the highest level of accuracy, the Grover model of 91.67%.